THE EFFECT OF FRAUD DIAMOND ON FRAUDULENT FINANCIAL STATEMENT IN ASIA PACIFIC COMPANIES - Sihombing, Tanggor; Cahyadi, Celine Celiana (Ultimaccounting Jurnal Ilmu Akuntansi, 2021)
Abstract - This study aims to determine how the influence of fraud diamonds in detecting fraudulent financial statements in companies in Asia-Pacific listed in S&P in 2017-2019. The study used a purposive sampling method with a total population of 228 companies with a sample of 78 companies and used the STATA program for analysis. The results of the hypothesis testing carried out were that the pressure on financial stability had an effect on fraudulent financial statements with a significant level of 0.000 which was smaller than the significant level in this study which was 0.0101 so that it is accepted with the understanding that financial assets in the company have an effect on committing fraud, the opportunity for the nature of industry to affect the fraudulent financial statement with a significant level of 0.001 where smaller than the significant level in this study which is 0.01 so it is accepted with the understanding that warehouse inventory can be a trigger for someone to commit fraud, the rationalization of total accruals has an effect on fraudulent financial statements with a significant level of 0.003 which is smaller than the significant level in this study which is 0.01 so it is accepted with the understanding that the total accruals owned by the company have an impact because someone can commit fraud by falsifying total accruals, and the ability to use a dummy has no effect on fraudulent financial statements with a significant level of 0.295 which is greater than the significant level in this study which is 0.01 so that it is rejected with the understanding that the change of directors is not a factor in someone committing fraud. Keywords: Financial Stability; Nature of Industry; Rationalization; Capability; Fraudulent Financial Statement